PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN DIVISI PRODUKSI CV. XYZ) - Gara, Made Adhika Laksamana Gara (Universitas Katolik Parahyangan, 2024)
This type of research uses quantitative research methods and is called applied research. Data is obtained using wawancara and kuesioner. The sample size for this research is all employees in the production division of CV. XYZ, which is about 45 people. The data that was obtained using the deskript analysis technique and the sederhana linear regression technique. The data analysis in this study was conducted using IBM SPSS 27. Based on the results of data entry, it can be observed that employee performance related to business performance is categorized as